A Robust, Safe, and Scalable Magnetic Nanoparticle Workflow for RNA Extraction of Pathogens from Clinical and Wastewater Samples (Global Challenges 4/2021). Issue 4 (7th April 2021) - Ramos‐Mandujano, Gerardo; Salunke, Rahul; Mfarrej, Sara; Rachmadi, Andri Taruna; Hala, Sharif; Xu, Jinna; Alofi, Fadwa S.; Khogeer, Asim; Hashem, Anwar M.; Almontashiri, Naif A. M.; Alsomali, Afrah; Shinde, Digambar B.; et al.
Abstract : A critical bottleneck in COVID‐19 diagnosis and surveillance is the shortage of kits for RNA extraction. In article number 2000068, Mo Li and co‐workers develop a DIY, open‐source, safe, and fast method for magnetic‐nanoparticle‐aided viral RNA isolation from contagious samples (MAVRICS). MAVRICS rivals commercial kits in performance and could become an enabling technology for community testing and wastewater monitoring in the current and future pandemics.